Advances in portfolio construction and implementation - Satchell, Stephen, 1949-; Scowcroft, Alan. (Amsterdam ; Oxford : Butterworth-Heinemann, 2003)
Modern Portfolio Theory explores how risk averse investors construct portfolios in order to optimize market risk against expected returns. The theory quantifies the benefits of diversification. Modern Portfolio Theory provides a broad context for understanding the interactions of systematic risk and reward. It has profoundly shaped how institutional portfolios are managed, and has motivated the use of passive investment management techniques, and the mathematics of MPT is used extensively in financial risk management. Advances in Portfolio Construction and Implementation o.
7.1 Introduction -- A Tractable N-Dimensional Experimental Control7.2 Applications; 7.3 Dynamic Constraints; 7.4 Results from the Dynamic Constraints Algorithm; 7.5 Problems and Limitations with Dynamic Constraints Algorithm; 7.6 Improvements to the Distribution; 7.7 Results of the Dynamic Constraints with Local Density Control; 7.8 Conclusions; 7.9 Further Work; 7.10 Appendix 1: Review of Holding Distribution in Low Dimensions with Minimal Constraints; 7.11 Appendix 2: Probability Distribution of Holding Weight in Monte Carlo Portfolios in N Dimensions with Minimal Constraints.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Portfolio management; Portfolio management -- Mathematical models; Investments; Investments; Gestion de portefeuille; Gestion de portefeuille -- Modèles mathématiques.; Investissements; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investments; Portfolio management; Portfolio management -- Mathematical models; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.